Histomorphometric of duodenum in male rabbits after fed commercial feed supplemented by cod liver oil - Ermayanti, Ni Gusti Ayu Manik; Sudatri, Ni Wayan; Wirasiti, Ni Nyoman; Widhyastini, I Gusti Ayu Manik (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i01.p10, 2021)
Fish oil is a source of long-chain polyunsaturated fatty acids (LCPUFA) that can be used as supplementary feed in commercial feed to increase male rabbit productivity. PUFAs function in various physiological processes, including in the digestive system.This study aimed to determine the histomorphometrics of male rabbits duodenum after fed commercial feed supplemented by cod liver oil. The experimental design used was a Completely Randomized Design (CRD) with four feed packages, namely commercial feed without cod liver oil (P0) as a control, commercial feed supplemented with cod liver oil 3% (P1), 4.5% (P2) and 6% (P3). Each consists of five male local rabbits as replicates and given starting female rabbits 1-3 months. The parameters observed were villi height, villi width, crypt depth, and tunica mucosa thickness of the duodenum in male rabbits. The data obtained were analyzed with Anova and if significantly different were further tested with DMRT. The results showed that cod liver oil supplementation in commercial feed was significantly different (p<0.05) to the histomorphometric parameters (villi height, villi width, crypt depth, and thickness of the tunica mucosa) of the duodenum in male rabbits. Can be concluted that supplementation of cod liver oil in commercial feed can increase the histomorphometrics of  male local rabbits duodenum.